2019
DOI: 10.1021/jacs.8b12506
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Transfer Hydrogenation with a Bifunctional Iron(II) Hydride: Experiment Meets Computation

Abstract: Hydride cis-β-[FeH(CNCEt 3 )(1)]BF 4 (5) (1 is a chiral N 2 P 2 macrocycle) is the catalytically active species in the asymmetric transfer hydrogenation of ketones formed upon reaction of [Fe(CNCEt 3 ) 2 ( 1)](BF 4 ) 2 (3) with base. Stoichiometric reactions show that hydride 5 is formed by H-elimination from the 2-propoxo complex [Fe(O i Pr)(CNCEt 3 )(1)]BF 4 (8a) and inserts the CO bond of acetophenone to give the diastereoisomeric alcoholato complexes [Fe(OCH(Me)Ph)-(CNCEt 3 )(1)]BF 4 (10R and 10S). Comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 103 publications
0
40
0
Order By: Relevance
“…Our previous studies have shown that the bulky isonitrile in the iron(II) analogue [Fe(CNCEt 3 ) 2 ( 1 )](BF 4 ) 2 is beneficial to enantioselectivity . The present DFT study reveals that attractive CH–π interactions between the substrate and 1 induce high enantioselectivity (≥90 % ee ) even without the assistance of bulky ancillary ligands and explain why aryl alkyl ketones are the substrates of choice.…”
Section: Figurementioning
confidence: 51%
“…Our previous studies have shown that the bulky isonitrile in the iron(II) analogue [Fe(CNCEt 3 ) 2 ( 1 )](BF 4 ) 2 is beneficial to enantioselectivity . The present DFT study reveals that attractive CH–π interactions between the substrate and 1 induce high enantioselectivity (≥90 % ee ) even without the assistance of bulky ancillary ligands and explain why aryl alkyl ketones are the substrates of choice.…”
Section: Figurementioning
confidence: 51%
“…This has been recently observed by Mezetti in a related context (ironmediated transfer hydrogenation of ketones using a secondary alcohol as hydrogen source), though basic conditions were required for the carbene formation to proceed. 30 As alkoxide species of the type [Ru(PNP H )(OR)(H)(CNR)] are most likely formed and involved in the catalytic cycle for alcohol dehydrogenative coupling, as in the case of carbonyl-based systems, 16d one may also envision an intramolecular deactivation pathway to access such carbene species. Alternatively, when investigating iron isonitrile complexes as catalysts for ketones transfer hydrogenation, Reiser and coworkers have also proposed that an intermediate iron hydride moiety reacts with isonitrile ligand, affording iminoformyl species 31 , similar to hydride migratory insertion into a carbonyl to form a acyl group.…”
Section: Catalytic Studies In Alcohol Acceptorless Dehydrogenationmentioning
confidence: 99%
“…95 Indeed, a mechanistic study shows that, also for this catalytic system, the active species is hydride [FeH(CNCEt 3 )(N 2 P 2 )]BF 4 , which is formed from the bis(isonitrile) complex in basic 2-propanol. 96…”
Section: Scheme 19 Ikariya's Catalyst For the Asymmetric Transfer Hydmentioning
confidence: 99%